2011
DOI: 10.1161/strokeaha.111.620179
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Memory Impairment Through the Interaction of Chronic Cerebral Hypoperfusion and Amlyloid Toxicity in a Rat Model

Abstract: Background and Purpose-Vascular pathology and Alzheimer disease (AD) pathology have been shown to coexist in the brains of dementia patients. We investigated how cognitive impairment could be exacerbated in a rat model of combined injury through the interaction of chronic cerebral hypoperfusion and amyloid beta (A␤) toxicity. Methods-In Wistar rats, chronic cerebral hypoperfusion was modeled by permanent occlusion of bilateral common carotid arteries (BCCAo). Further, AD pathology was modeled by bilateral intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 42 publications
7
59
0
1
Order By: Relevance
“…Consistent with previous studies, 7 we confirmed the presence of memory impairments using the water maze task and novel object test in a rat model of chronic cerebral hypoperfusion. Poor performance in the odor discrimination task suggests that cognitive functions associated with olfaction were also impaired in a rat model of chronic cerebral hypoperfusion.…”
Section: Cognitive Impairments Induced By Chronic Cerebral Hypoperfusionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, 7 we confirmed the presence of memory impairments using the water maze task and novel object test in a rat model of chronic cerebral hypoperfusion. Poor performance in the odor discrimination task suggests that cognitive functions associated with olfaction were also impaired in a rat model of chronic cerebral hypoperfusion.…”
Section: Cognitive Impairments Induced By Chronic Cerebral Hypoperfusionsupporting
confidence: 92%
“…6 For chronic cerebral hypoperfusion, rats subjected to permanent occlusion of the bilateral common carotid arteries (BCCAo) were used, which has been previously suggested as a possible animal model for vascular dementia. 7,8 As time went on after the surgery, cerebral blood flow and metabolism decreased chronically in our previous study 7 ( Figure I in the online-only Data Supplement). In this study, we investigated cognitive impairment and its association with disintegration of diverse white matter components.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…We also predicted that decreased metabolism in the hippocampal region would be found in proportion to the degree of cardiovascular risk, given both the relevance of this brain region as a critical site of neuropathological AD changes, as well as its particular vulnerability to chronic blood flow deficits in animal models of brain hypoperfusion (Wang et al 2010;Choi et al 2011). Rather unexpectedly, we actually found relatively increased brain metabolism in a voxel cluster located in the parahippocampal gyrus both in the comparisons across three groups and in the high-risk group when compared to the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Since the establishment of two-vessel occlusion (2VO), which is the permanent bilateral occlusion of the common carotid artery, in rats as an animal model to reproduce CCH (51,52), this model has been widely used to study the molecular mechanisms underlying the cognitive impairment, white matter lesions, and neuronal damage observed in CCH, as well as in therapeutic intervention studies (16,34,35,65). Generation and accumulation of amyloid and injury to white matter integrity and glial activation, which result in cognitive impairment, have also been observed in the 2VO rat model (29).…”
Section: Innovationmentioning
confidence: 99%